2021
DOI: 10.1038/s41391-021-00478-2
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance inclusion criteria under scrutiny in magnetic resonance imaging-guided prostate biopsy: a multicenter cohort study

Abstract: Background Although multiparametric magnetic resonance imaging (mpMRI) is recommended for primary risk stratification and follow-up in Active Surveillance (AS), it is not part of common AS inclusion criteria. The objective was to compare AS eligibility by systematic biopsy (SB) and combined MRI-targeted (MRI-TB) and SB within real-world data using current AS guidelines. Methods A retrospective multicenter study was conducted by a German prostate cancer (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For example, a recent randomized control trial found that mpMRI in combination with TRUS/MRI fusion biopsies detected 12% more clinically significant cancers and 13% less indolent prostate cancers than systematic biopsy and resulted in 28% fewer biopsies being performed overall [41]. Other work has demonstrated the integral role of mpMRI in active surveillance, with MRI-guided targeted biopsies demonstrating clinically significant prostate cancer in 32% of patients previously classified as eligible for active surveillance on systematic biopsy [42]. Lesions selected for biopsy are categorized via the PI-RADS scoring scheme, which has been validated in several studies and demonstrated moderate interobserver variability [26,43,44].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…For example, a recent randomized control trial found that mpMRI in combination with TRUS/MRI fusion biopsies detected 12% more clinically significant cancers and 13% less indolent prostate cancers than systematic biopsy and resulted in 28% fewer biopsies being performed overall [41]. Other work has demonstrated the integral role of mpMRI in active surveillance, with MRI-guided targeted biopsies demonstrating clinically significant prostate cancer in 32% of patients previously classified as eligible for active surveillance on systematic biopsy [42]. Lesions selected for biopsy are categorized via the PI-RADS scoring scheme, which has been validated in several studies and demonstrated moderate interobserver variability [26,43,44].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Furthermore, it has been suggested that MRI-targeted biopsy may increase overtreatment associated with PSA testing by detecting small amounts of Gleason grade 4 cancer that may have been missed by systematic biopsy and are unlikely to cause harm. 17 19 This may lead to ‘upgrading’ of patients who would otherwise be considered low risk (Gleason 6 [3 + 3]), changing their management from active surveillance to radical treatment. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Its implementation mitigates the burden of overtreatment that up to 20%–50% newly diagnosed men may experience 3 . However, identification and monitoring strategies of patients who may benefit from AS remain challenging 4 …”
Section: Introductionmentioning
confidence: 99%
“…3 However, identification and monitoring strategies of patients who may benefit from AS remain challenging. 4 AS protocols require a multimodal assessment based on clinical parameters (digital rectal examination [DRE]), laboratory testing (prostate-specific antigen [PSA]), imaging (multiparametric magnetic resonance imaging [mpMRI]), as well as patient willingness to continue surveillance. 5 Since mpMRI introduction in prostate examination, it has been shown to improve the detection of clinically significant prostate cancer (csPCa) and reduce the diagnosis of indolent disease.…”
Section: Introductionmentioning
confidence: 99%